Microbial interactions in the rumen - Dehority, Burk (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
Numerous interaction have been observed between the three largest groups of microorganisms that exist in the rumen, i.e., protozoa, bacteria and fungi. Many of these interactions may be negative by nature and have been observed only in vitro, or they are based on limited live observations. These interactions are briefly outlined and a short discussion of each is presented. Since these three types of microorganisms possess similar metabolic capacities, a negative interaction between two of them may not be reflected in a disminution of digestion in the rumen because this activity is simply controlled by another organism. Or: the other hand, the different enzyme activities that occur between types and species of organisms result in a distinct synergism and crossed feeding. This could in the end be beneficia1 to the animal host through increases in the digestibility and diet utilization.